2023
DOI: 10.1002/smll.202208077
|View full text |Cite
|
Sign up to set email alerts
|

Combining Highly Dispersed Amorphous MoS3 with Pt Nanodendrites as Robust Electrocatalysts for Hydrogen Evolution Reaction

Abstract: Surface modification of electrocatalysts to obtain new or improved electrocatalytic performance is currently the main strategy for designing advanced nanocatalysts. In this work, highly dispersed amorphous molybdenum trisulfide‐anchored Platinum nanodendrites (denoted as Pt‐a‐MoS3 NDs) are developed as efficient hydrogen evolution electrocatalysts. The formation mechanism of spontaneous in situ polymerization MoS42− into a‐MoS3 on Pt surface is discussed in detail. It is verified that the highly dispersed a‐Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…33 Generally, the Tafel curves were plotted according to the following equation: η = a + b log( j ), where a represents the intercept, b is the Tafel slope, and j is the current density. 30,34 It can be found that only the Tafel slope of Pt 42 Ni 58 (31.15 mV dec −1 ) in the acidic electrolyte was higher than 30 mV dec −1 and hydrogen evolution reaction may follow the Volmer–Heyrovsky mechanism, while the HER process of the other catalysts followed the Volmer–Tafel pathway. In contrast to Pt 42 Ni 58 , which was limited by the slow kinetics of the electrochemical desorption step: M − H ads + H + + e − = M + H 2 (Heyrovsky reaction), the synergistic effect of Pt and Ni in Pt 12 Ni 88 and Pt 23 Ni 77 facilitated the electrochemical discharge step of the catalyst with H + :M + H + + e − = M − H ads , leading to a change in the rate determining step of the hydrogen precipitation reaction to an electrochemical desorption step: 2M −H ads = 2M + H 2 (Tafel reaction).…”
Section: Resultsmentioning
confidence: 99%
“…33 Generally, the Tafel curves were plotted according to the following equation: η = a + b log( j ), where a represents the intercept, b is the Tafel slope, and j is the current density. 30,34 It can be found that only the Tafel slope of Pt 42 Ni 58 (31.15 mV dec −1 ) in the acidic electrolyte was higher than 30 mV dec −1 and hydrogen evolution reaction may follow the Volmer–Heyrovsky mechanism, while the HER process of the other catalysts followed the Volmer–Tafel pathway. In contrast to Pt 42 Ni 58 , which was limited by the slow kinetics of the electrochemical desorption step: M − H ads + H + + e − = M + H 2 (Heyrovsky reaction), the synergistic effect of Pt and Ni in Pt 12 Ni 88 and Pt 23 Ni 77 facilitated the electrochemical discharge step of the catalyst with H + :M + H + + e − = M − H ads , leading to a change in the rate determining step of the hydrogen precipitation reaction to an electrochemical desorption step: 2M −H ads = 2M + H 2 (Tafel reaction).…”
Section: Resultsmentioning
confidence: 99%
“…nucleation process). 25 However, DMA has a higher solubility than DMF that can boost the uniform dispersion of Fe 3+ , Co 2+ and BDC-NH 2 in the solution as well as enhance the mass transfer rate ( i.e. crystal growth process).…”
Section: Resultsmentioning
confidence: 99%
“…Xu's group illustrated through density functional theory (DFT) calculations that the Pt atom at the α-MoS 3 /Pt interface serves as a preferred active site for the highly efficient transition of hydrogen ions to hydrogen, promoting Pt-α-MoS 3 to exhibit excellent HER performance at all pH levels. 25 Considering the ultra-high activity and conductivity of the active sites at the heterointerface, the number or density of heterointerfaces is considered to be crucial for improving the catalytic performance. Qin et al synthesized (Fe x Co 1− x ) 2 B catalysts with controllable grain boundary density by ball milling.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous electrocatalysts, as a special type of catalyst, have been extensively studied for their uniqueness and attractiveness in the HER. 10–13 Amorphous catalysts have a larger electrochemical active area (ECSA) than crystalline electrocatalysts, providing the advantage of a larger electrolyte–electrocatalyst interface and high corrosion resistance to the HER. 14,15 The amorphous CoS X catalyst has been prepared via electrodeposition by Kornienko et al , and its high HER activity is attributed to the formation of CoS 2 -like molecular clusters after cathodic polarization, with a high density of sulfur atoms present at the periphery of the cluster.…”
Section: Introductionmentioning
confidence: 99%